The Challenges of Youth Entrepreneurship from a Local Government Perspective in South Africa - Nduduzo C Ndebele; Sbonelo G Ndlovu; Victor H Mlambo; Xolani Thusi (Research Synergy Foundation, 2022)
This paper examines the challenges of youth entrepreneurship and aims to understand whether the local government sector in South Africa can act as a catalyst in consolidating youth entrepreneurship. The local government sector is essential in South Africa as it is mandated to grow and improve local infrastructure and community services and contribute towards economic development. Opening opportunities for young people in the entrepreneurship domain can help reduce unemployment. Through funding and training opportunities, the local government sector, a branch of government closer to the people, can play a significant role in fostering youth entrepreneurship. A qualitative research approach was employed where a literature review was untaken. Findings revealed that an increasing youth unemployment rate faced South Africa, negatively affecting the need for inclusive development. The paper found that local government can contribute towards reducing youth unemployment by implementing programs encouraging and capacitating youth entrepreneurship and prioritizing entrepreneurship education. However, it was also revealed that the local government sector is confronted with several challenges, such as corruption, wasteful expenditure, and a lack of skilled personnel. Unless these issues are addressed, it will be impossible for the sector to consolidate policies that support and encourage youth entrepreneurship. Keywords: Entrepreneurship; Development; Inclusive; Support; Unemployment; Youth